Peta Pengetahuan Penelitian Deforestasi dan Bencana di Indonesia: Analisis Bibliometrik dan Implikasi Transformasi Digital - Mahmud, Muslimin; Supriyadi, Asep Adang (PendIPA Journal of Science Education, 2026)
Indonesia's forests play a strategic role in maintaining ecosystem balance, but increasing deforestation and land degradation have increased the risk of environmental disasters, particularly flooding in Sumatra. As scientific attention has increased, research on Indonesian forests has grown rapidly but remains multidisciplinary and fragmented. This study aims to map the knowledge structure, thematic dynamics, and patterns of global collaboration in deforestation and disaster research in Indonesia, and to examine the integration of digital transformation into these studies. This study uses a descriptive quantitative approach through bibliometric analysis of 175 Scopus-indexed journal articles extracted using the keyword "Indonesian forest." The analysis was conducted using VOSviewer to map keyword co-occurrence and author collaboration by country, and to interpret the role of digital technologies such as Geographic Information Systems (GIS), remote sensing, and spatial analysis. The analysis shows that deforestation and forest fires are dominant themes closely related to disaster risk, air pollution, and health impacts. Digital technologies, particularly remote sensing and GIS, have become key methodological components in forest cover monitoring, carbon emission analysis, and flood-prone area mapping in Sumatra. Indonesia occupies a central position in global collaboration networks, with strong involvement from countries with high technological capacity, although the use of predictive and early warning systems remains relatively limited. The novelty of this research lies in the integration of bibliometric analysis with disaster and digital transformation perspectives, linking the thematic structure of research, international collaboration patterns, and their implications for flood mitigation in Sumatra. These findings provide important contributions to the development of forestry research and policy, and the strengthening of digital transformation in forest management and disaster risk reduction in Indonesia.